2004
DOI: 10.1111/j.1442-2018.2004.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Validating the revised Health Belief Model for young families: Implications for nurses’ health promotion practice

Abstract: By modifying the Health Belief Model (HBM) nurses can provide health promotion guidance for families through the revised HBM for young families. The constructs 'perceived behavioral control' and 'behavioral intention' from Ajzen's Theory of Planned Behavior were added to the HBM to provide a health orientation. An initial qualitative study informed the second quantitative study through thematic data obtained by interviewing parents about family health. The second comparative study of low and high socioeconomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(37 reference statements)
3
8
0
Order By: Relevance
“…Statistical analysis performed in the course of this study confirmed the positive influence of perceived susceptibility on intention to be consistent with previous studies [44,21]. The organisation"s or department"s susceptibility to fraud will increase the intention of using forensic accounting services in fraud prevention.…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Statistical analysis performed in the course of this study confirmed the positive influence of perceived susceptibility on intention to be consistent with previous studies [44,21]. The organisation"s or department"s susceptibility to fraud will increase the intention of using forensic accounting services in fraud prevention.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…Accordingly, the influence of perceived susceptibility to fraud has been confirmed in literature [21,[41][42][43][44][45]. The influence of perceived severity of fraud on behavioural intention has also been confirmed in the literature [44][45][46]. Therefore, the present study also believes that threat perception is a key predictor for the use forensic accounting techniques and two propositions have been proposed.…”
Section: Influence Of Threat Perception Factors On Behavioural Intentsupporting
confidence: 75%
“…Roden (2003) found that parents who were of a higher socioeconomic level believed that they were able to perform child health promoting activities more than those who had lower income. The majority of the participants in this car seat study had high income.…”
Section: Discussionmentioning
confidence: 97%
“…Moderator will use an interview protocol written based on responsive interviewing model (15). A protocol which consisted of a list of questions was developed based on Health Belief Model (HBM) domain framework (16) was used to introduce areas for open discussion. Since this study is keen to see how respondent would interact during the focus group, group dynamic and interactions were enhanced by reassuring all respondents that any views expressed in the focus group would remain confidential and that there were no 'right' or 'wrong' answers to the questions and that constructive criticism was a valued part of the process.…”
Section: Focus Group Discussionmentioning
confidence: 99%
“…HBM is the earliest theory developed to explain the process of lifestyle adoption and individual's behavioural choice. In the theory, three domains are suggested as the initiator in lifestyle and behaviour choices; motivations, perceived barriers and perceived threat (16). This study adopted HBM as the fundamental framework to understand nutrition and lifestyle behaviour of Malaysian adults with MetS.…”
Section: Discussionmentioning
confidence: 99%